Effects of three modified plyometric depth jumps and periodized weight training on lower extremity power - Andrew, D. P. S.; Heitman, R. J.; Robinson, T. L. (The Sport Journal, 2010)
Plyometric exercises increase muscular power and are most effective when designed to complement the specific movements required of the athletic activity. This study compared the effects of modified depth jump plyometric exercises versus a periodized weight training program on the following functional tests: one-legged vertical jump, two-legged vertical jump, 30-meter sprint, standing broad jump, and 1 RM of the seated single leg press. Sixty-four untrained participants (18-28yr) were randomly assigned to one of the following groups: hip depth jump (n = 12), knee depth jump (n = 13), ankle depth jump (n = 13), weight training (n = 13), or a control (n = 13). Experimental groups trained two days a week for 12 weeks. Statistically significant improvements were observed among the plyometric groups for functional tests of power and the weight training group for functional tests of strength and speed. Results indicate that modified plyometric depth jumps offer a greater degree of specificity related to power training in athletes.